CHARACTERIZATION AND STRENGTH ANALYSIS OF REINFORCED BAMBOOS AND BAMBOOS WITHOUT REINFORCEMENTS - L, Gyansah; I.A, Adetunde (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
This paper investigates the strength of reinforced fresh, reinforced dried and bamboos without reinforcement subjected to static loading condition. Crushing strength test was performed using uniaxial compression machine with maximum loading capacity of 1500 KN. The data is plotted as failure stress to height, specific compressive strength with height, strength to weight ratio versus height, strength to volume ratio versus height. Result shows that the strength increases as the height increases for all structures analysed. All the bamboo structures exhibited elastic behaviour, but the reinforced fresh bamboo showed higher elastic behavior to the transition point. The dried reinforced bamboo proves to have the highest intrinsic strength beyond the transition point. Failure stress to weight ratio also decreases with increases with height for all cases of the structures. The specific compressive strength of both non-reinforced fresh and dried has an appreciable increased up to a transition point and then it decreased with increased with height. Failure stress proves that the strength of reinforced dried bamboo increases with increases in height. Conclusively, the reinforced dried bamboo can withstand higher compressive load than the rest of the bamboo structures